ANALISIS KESALAHAN DAN SCAFFOLDING SISWA BERKEMAMPUAN RENDAH DALAM MENYELESAIKAN OPERASI TAMBAH DAN KURANG BILANGAN BULAT - Lailatul Badriyah; Abdur Rahman As’ari; Hery Susanto (Graduate School of Universitas Negeri Malang, 2017)
This study aims to find out the error made by the low achievement students in completing the operation of adding and subtracting integers as well as scaffolding to help studenst correct thire errors. Researchers gave 7 items about integer arithmetic operations to 20 students of class VIII. The errors contained in the low achievement student worksheets were then analyzed and used as the basis for on-to-one scaffolding. The results showed that the pattern of students' error in completing the operation of adding and subtracting integers is that they neglect the minus sign in the negative numbers. Scaffolding to help the low ability students improve their knowledge and fix their errors in completing the the operation of adding and subtracting integers are the level 2 (Reviewing and Restructuring), and level 3 (Making Connection) scaffolding.Penelitian ini bertujuan untuk mengetahui kesalahan yang dilakukan siswa berkemampuan rendah dalam menyelesaikan operasi tambah dan kurang bilangan bulat serta scaffolding yang dapat membantu siswa memperbaiki kesalahan tersebut. Peneliti memberikan 7 butir soal operasi hitung bilangan bulat kepada 20 siswa kelas VIII. Kesalahahan yang terdapat pada lembar kerja siswa berkemampuan rendah dianalisis dan digunakan sebagai dasar pemberian on-to-one scaffolding. Hasil penelitian menunjukkan bahwa pola kesalahan siswa dalam menyelesaikan operasi kurang bilangan bulat adalah pengabaian lambang minus pada bilangan negatif. Sescaffolding yang dapat membantu siswa berkemampuan rendah meningkatkan pengetahuan dan memperbaiki kesalahan dalam menyelesaikan operasi tambah dan kurang bilangan bulat adalah scaffolding level 2 reviewing dan restructuring dan level 3 (Making Connections).